The characteristics of high performing supply chains. (1st January 2000) - Oliver, Nick; Delbridge, Rick
This paper contrasts the characteristics of high and low performing supply chains in Japan, the US and Europe. From an initial set of 20 supply chains (all of which produced brake products for the automotive industry) six "high" and six "low" performing chains were identified, based on their levels of performance on quality (defect rates) and on-time delivery. Comparison of the characteristics of the two groups reveals that, on average, the high performing supply chains have lower inventories, more frequent deliveries, a higher number of second tier suppliers (but serve the same number of car makers) and have higher production volumes. They also possess more sophisticated and active structures for information exchange and learning. Supply chains located in Japan are considerably over-represented in the high performing category, but interview data revealed the danger of equating the long-term relationships found in Japan with "cosiness" between car makers and suppliers. The characteristics of both high and low performing supply chains appear to be shaped by a variety of contingencies, and exploration of these contingencies is a fruitful avenue for future research.